Design, Synthesis, and Aqueous Aggregation Behavior of Nonionic Single and Multiple Thermoresponsive Polymers - Skrabania, Katja; Kristen, Juliane; Laschewsky, André; Akdemir, Özgür; Hoth, Ann; Lutz, Jean-François (Langmuir, 2007)
Nonionic water-soluble poly(acrylamide)s and poly(acrylate)s were synthesized by RAFT and ATRP methods. Similar to the synthesized poly(N-isopropylacrylamide) and poly(N-acryloylpyrrolidine), aqueous solutions of statistical acrylate copolymers bearing two different oligo(ethylene oxide) side chains showed a sharp clouding transition upon heating beyond characteristic temperatures. The temperature of the cloud point can be easily fine tuned by the copolymer composition. As for poly(N-isopropylacrylamide) and poly(N-acryloylpyrrolidine), the cloud-point temperatures of these statistical copolymers are rather insensitive to changes in the molar mass or the NaCl content of the solutions. Also, ternary triblock copolymers containing one permanently hydrophilic block and two different thermoresponsive blocks were synthesized, varying the block sequence systematically. Their aggregation in aqueous solution was followed by turbidimetry and dynamic light scattering. Depending on the heating process and the triblock sequence, micellar aggregates of 40 to 600 nm size were found. The thermally induced aggregation behavior depends sensitively on the block sequence but is also subject to major kinetic effects. For certain block sequences, a thermally induced two-step association is observed when heating beyond the first and second cloud points of the thermoresponsive blocks. However, the thermal-transition temperatures of the block polymers can differ from the thermal-transition temperatures of the individual homopolymers. This may be caused by end-group effects but also by mutual interactions of the different blocks in solution, as physical mixtures of the homopolymers exhibit deviations from a purely additive thermal behavior.